(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Small mammals are essential components of tropical rainforest ecosystems and hold potential to support biodiversity-based ecotourism through engaging wildlife encounters. This study assessed species richness, composition, and beta diversity of small mammals in Sedim River Forest Eco Park, Peninsular Malaysia as well as their guild-specific detection pattern. Systematic sampling was conducted within a 400 m × 200 m plot using 100 collapsible cage traps, three harp traps, and 10 mist nets over five sampling sessions, each comprising five consecutive nights. Opportunistic observations were also carried out. A total of 26 species from 10 families were recorded. Live trapping captured 113 individuals representing 18 species, with Hipposideros larvatus being the most common. Direct observation yielded six individuals of six distinct arboreal species, with no overlap between methods, highlighting the complementary value of both methods. Diversity indices across sessions ranged from 0 to 2.53 (Shannon–Weiner), 0 to 0.9021 (Simpson), and 0.628 to 1.0 (evenness), with peak diversity during Session 3. A significant association was found between the sampling method and ecological guild (χ² = 45.61, df = 2, p < 0.001). Beta diversity analysis using the Bray-Curtis Similarity Index revealed that the small mammal community in Gunung Inas FR (where Sedim River Forest Eco Park is located) was more similar to Padang Chong FR (43.2%) than Ulu Muda FR (29.3%), supported by a shared species count of 12. These findings demonstrate the importance of multi-method sampling and highlight the potential of diverse small mammal communities as valuable assets in low-impact ecotourism and conservation planning.